Identification of Molecular Signatures and Candidate Drugs in Vascular Dementia by Bioinformatics Analyses - Shu, Jun; Wei, Wenshi; Zhang, Li (Frontiers in Molecular Neuroscience, 2022)
Vascular dementia (VaD) is considered to be the second most common form of dementia after Alzheimer's disease and no specific drugs have been approved for VaD treatment. We aimed to identify shared transcriptomic signatures between the frontal cortex and temporal cortex in VaD by bioinformatics analyses. Gene ontology and pathway enrichment analyses, protein–protein interaction (PPI) and hub gene identification, hub gene–transcription factor interaction, hub gene–microRNA interaction, and hub gene–drug interaction analyses were performed. We identified 159 overlapping differentially expressed genes (DEGs) between the frontal cortex and temporal cortex that were enriched mainly in inflammation and innate immunity, synapse pruning, regeneration, positive regulation of angiogenesis, response to nutrient levels, and positive regulation of the digestive system process. We identified ten hub genes in the PPI network (GNG13, CD163, C1QA, TLR2, SST, C1QB, ITGB2, CCR5, CRH, TAC1), four central regulatory transcription factors (FOXC1, CREB1, GATA2, HINFP), and four microRNAs (miR-27a-3p, miR-146a-5p, miR-335-5p, miR-129-2-3p). Hub gene–drug interaction analysis found four drugs (maraviroc, cenicriviroc, PF-04634817, efalizumab) that could be potential drugs for VaD treatment. Together, our results may contribute to understanding the underlying mechanisms in VaD and provide potential targets and drugs for therapeutic intervention.